RAB18, a protein associated with Warburg Micro syndrome, controls neuronal migration in the developing cerebral cortex. Issue 1 (December 2016) - Wu, Qinwei; Sun, Xiaqin; Yue, Weihua; Lu, Tianlan; Ruan, Yanyan; Chen, Tianda; Zhang, Dai
Abstract Background Loss of function mutations in RAB18, has been identified in patients with the human neurological and developmental disorder Warburg Micro syndrome. However, the function of RAB18 in brain remains unknown. Results In this study, we report that RAB18 is a critical regulator of neuronal migration and morphogenesis. Using in utero electroporation suppression of RAB18 in the mouse brain impairs radial migration. Overexpression of dominant negative RAB18 or disruption of RAB3GAP (RAB18GEF) also results in delayed neuronal migration in the developing mouse cortex and inhibition of neurite growth in vitro. Moreover, loss of RAB18 induces an acceleration of N-cadherin degradation by lysosomal pathway resulting in the decrease of surface level of N-cadherin on neurons. Conclusions RAB18 regulates neuronal migration and morphogenesis during development. Our findings highlight the critical role of RAB3GAP-RAB18 pathway in the developing cerebral cortex and might explain some of clinical features observed in patients with Warburg Micro syndrome.